Bovine Leptospirosis Due to Persistent Renal Carriage of Leptospira borgpetersenii Serovar Tarassovi - Hamond, Camila; LeCount, Karen; Putz, Ellie J.; Bayles, Darrell O.; Camp, Patrick; Goris, Marga G. A.; van der Linden, Hans; Stone, Nathan E.; Schlater, Linda K.; Sahl, Jason W.; Wagner, David M.; Nally, Jarlath E. (Frontiers in Veterinary Science, 2022)
Leptospirosis is a global zoonotic disease that causes significant morbidity and mortality in human and animal populations. Leptospira interrogans is a leading cause of human disease, and L. borgpetersenii is a leading cause of animal disease. Cattle are reservoir hosts of L. borgpetersenii serovar Hardjo, which is transmitted via urine, semen, and uterine discharges resulting in abortion and poor reproductive performance. Bovine bacterin vaccines can only protect against those serovars included in vaccine formulations and typically include serovar Hardjo among others. Genotyping and serotyping represent two different and unique methods for classifying leptospires that do not always correlate well; comprehensive characterization using either method requires recovery of isolates from infected animals. In this study, we report for the first time, isolation of L. borgpetersenii serovar Tarassovi from the urine of a dairy cow in the U.S. The classification of the isolate, designated strain MN900, was confirmed by whole-genome sequencing, serotyping with reference antisera and monoclonal antibodies, Matrix Assisted Laser Desorption/Ionization (MALDI), and immunoblotting with reference antisera. Strain MN900 was excreted in urine samples for 18 weeks even as the cow was seronegative for serovar Tarassovi. Strain MN900 has an unusual morphology since it is not as motile as other leptospires and lacks hooked ends. Serovar Tarassovi is not included in U.S. bacterin vaccines. These results demonstrate the importance of culture and concomitant genotyping and serotyping to accurately classify leptospires, and as required to design efficacious vaccine and diagnostic strategies to not only limit animal disease but reduce zoonotic risk.